Kontroversi Perda Berbasis Syariah Dalam Otonomi Daerah Di Indonesia - Mufidah, Mufidah; Hejazziey, Djawahir; Sari, Novi Yuspita (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2021)
Article 29 paragraph 1 of the 1945 Constitution of the Republic of Indonesia states that